Cultural Heritage And Creative Arts Development - M Guntoro; Zuki Kurniawan; Mia Rosalina (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
Indonesia has cultural diversity that is the pride of the Indonesian people. Indonesian culture has its unique variations and types. However, the development of the times and the era of openness have led to the entry and development of foreign cultures, which are more in demand by some people because they regard foreign cultures as modern. This results in the younger generation preferring a new culture which may be considered more attractive and practical compared to the local culture. This cultural diversity cannot be separated from the creative economy, which is believed to be a new wave in world economic trends after the biotechnology, information and communication era. As a new wave in the world's thought discourse, it raises various pros and cons from various groups and organizations. This research uses a descriptive analysis method. The research results and discussion show that creative economy-based industries can be developed more broadly using a culture-based approach. With its enormous cultural wealth, Indonesia has great potential and opportunity to become the centre of the world's creative economy. Technological developments in the Industry 4.0 era brought about many changes, especially in the creative industry, where there were many creative industry fields whose developments were greatly assisted by the presence of the Industry 4.0 era.